High-frequency acoustic wave properties in a water-filled pipe. Part 1: dispersion and multi-path behaviour. Issue 5 (3rd September 2017) - Louati, Moez; Ghidaoui, Mohamed S.
ABSTRACT: Defect resolution using transient-based detection methods (TBDDM) improves as frequency bandwidth of injected signals increases. High-frequency waves (HFW) excite radial and azimuthal modes, however, making the 1D water-hammer ineffective for these phenomena. This paper focuses on idealized HFW in inviscid, slightly compressible fluid in rigid, unbounded, circular conduits. HFW waves are generated by an axisymmetric wave source. High-order 2D finite volume scheme is developed for HFW. Results show that injected probing waves containing a cut-off frequency exhibit significant wave dispersion, and group velocity varies over a wide range of speeds, resulting in wave-energy spatial spreading with large amplitude reduction. Injected signals without any cut-off frequency remain spatially separated. Size of wave source significantly affects energy distribution within wave modes. Practical implications are that probing wave and defect resolution effectiveness may be increased using (i) probing HFW without cut-off frequencies contained in the bandwidth of the injected probing signal, and (ii) larger power sources for the injection of probing wave signals.